2016
DOI: 10.1093/infdis/jiw197
|View full text |Cite
|
Sign up to set email alerts
|

VAR2CSA Domain-Specific Analysis of Naturally Acquired Functional Antibodies toPlasmodium falciparumPlacental Malaria

Abstract: Broadly neutralizing antibodies of multigravidae are not depleted on VAR2CSA recombinant antigens, and hence development of VAR2CSA vaccines based on a single construct and variant might induce antibodies with limited broadly neutralizing activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 48 publications
5
32
1
Order By: Relevance
“…In this study, high levels of antibody reactivity to recombinant DBL3 FCR3 were associated with greater BIA against NF54 but not against the FCR3 isolate. This observation is consistent with our previous report showing that anti-DBL3 antibodies purified from multigravidae had no BIA against the homologous isolate yet disrupted binding of a heterologous parasite to CSA (16). This unexpected failure of BIA against the homologous FCR3 parasite may be explained by allele-specific nonfunctional anti-DBL3 FCR3 antibodies that impede the binding of functional antibodies (51), but this hypothesis requires additional study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, high levels of antibody reactivity to recombinant DBL3 FCR3 were associated with greater BIA against NF54 but not against the FCR3 isolate. This observation is consistent with our previous report showing that anti-DBL3 antibodies purified from multigravidae had no BIA against the homologous isolate yet disrupted binding of a heterologous parasite to CSA (16). This unexpected failure of BIA against the homologous FCR3 parasite may be explained by allele-specific nonfunctional anti-DBL3 FCR3 antibodies that impede the binding of functional antibodies (51), but this hypothesis requires additional study.…”
Section: Discussionsupporting
confidence: 92%
“…Here, the parity-related functional antibody activity appeared to be significantly shaped by the parasite variant. Prior studies have described variant-specific BIA and OA of naturally acquired antibodies in pregnant women (16,35) although related data assessing these two functions of antibodies in the same samples are absent. Plasma BIA in multigravidae was significantly higher against NF54 parasites, and plasma OA was significantly higher against FCR3 parasites than in primigravidae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent findings indicate that broadly neutralising antibodies of multigravidae are not depleted on VAR2CSA recombinant antigens. Using a new approach to assess VAR2CSA domains for functional epitopes recognized by naturally acquired antibodies, Doritchamou et al (2016) recently demonstrated that different Duffy binding-like (DBL) domain-specific IgG could react to both homologous as well as heterologous antigens and parasites, suggesting that conserved epitopes are shared between allelic variants. In addition, IE binding was blocked by ID1-DBL2-ID2a, DBL4 and DBL5-specific IgG, while partial cross-inhibition activity was observed with purified IgG specific to ID1-DBL2-ID2a and DBL4 antigens.…”
Section: Pathologies Other Than Cm: Mipmentioning
confidence: 99%
“…Microbes can also induce suppression, blocking [4], impeding [5,6] and many other escape mechanisms [7] rendering new or previously acquired immunity useless.…”
Section: A N U S C R I P Tmentioning
confidence: 99%